Influence of problem-based learning games on effective computer programming learning in higher education - Chang, Chiung-Sui; Chung, Chih-Hung; Chang, Julio Areck (Educational technology research and development, 2020)
Gaming is a part of today’s society, especially for younger generations. Therefore, game-based approaches are unsurprisingly used for learning achievement. In this study, a game-based learning courseware was implemented using a problem-based strategy. For this purpose, a game known as ‘Programmer Adventure Land’ was designed and developed. A group of college students were asked to play the game to improve their knowledge of computer programming. Results indicated that the problem-based learning approach of the game can enhance the satisfaction, enjoyment, motivation, and user interface for the problem-based game learning courseware. The main finding of this study is that Problem-based games provide teachers with an effective approach for enhancing students’ learning satisfaction in difficult subjects, such as computer programming.